Challenges in The Implimentation of Mother Tongue Education in Nigerian Schools: the Way Forward - Salihu Mahuta, Adamu (MultiTech Publisher, 2023)
The paper focuses on the use of mother tongue as a medium of instruction at pre-primary and primary levels of education is very vital for educational development of our children. Researches have shown that the child learns better and quicker his mother tongue is used in instruction than using a foreign language (English). This paper discusses the provision made by national policy on education (NPE) on the relevance and importance of mother tongue in education. It also highlights the benefit of mother tongue as a medium of instruction at both pr-primary and primary levels. In addition, the challenges of implementation of mother tongue education are not left un discussed, the effective way to the implementation of mother tongue education in Nigeria, finally followed by the conclusion.